2008
DOI: 10.1161/circulationaha.107.718874
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Cytomegalovirus Replication in Pediatric Heart Transplantation

Abstract: Background-Cardiac allograft vasculopathy is the major limiting factor to the long-term success of pediatric heart transplantation. Cytomegalovirus (CMV) has been shown to be a significant risk factor for the development of cardiac allograft vasculopathy. Recent work has demonstrated CMV DNA in leukocytes in the absence of direct allograft infection, suggesting that vascular changes may not be limited to the allograft. Method and Results-Systemic arterial endothelial function was assessed with high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…Recently, investigators have suggested that CMV replication results in endothelial dysfunction as measured with brachial artery flowmediated dilation in children after heart transplantation. 11 Some studies in adults demonstrated that recipient seropositivity status was correlated with either overt CAV detected by coronary angiography or more rapid lumen loss identified by intravascular ultrasound. [12][13][14] Until recently, little had been reported about the relationship of CMV serology and clinical outcomes in pediatric heart transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigators have suggested that CMV replication results in endothelial dysfunction as measured with brachial artery flowmediated dilation in children after heart transplantation. 11 Some studies in adults demonstrated that recipient seropositivity status was correlated with either overt CAV detected by coronary angiography or more rapid lumen loss identified by intravascular ultrasound. [12][13][14] Until recently, little had been reported about the relationship of CMV serology and clinical outcomes in pediatric heart transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological factors leading to endothelial dysfunction that are especially relevant to the development of vascular disease include the following (2, 43, 213, 330, 338, 492, 493): Activation by cytokines;Stimulation by free radicals/ROS or oxidative stresses and the advanced glycation end products generated in diabetes and aging;Chronic smoking and hypertension;Chronic exposure to hyperhomocysteinemia and/or hypercholesterolemia;Increased plasma levels of oxidized low-density lipoprotein (LDL) and its accumulation within the vessel wall, as well as infection by bacteria, viruses, and other pathogens with the release of their products (251, 435, 528, 618). …”
Section: Hemodynamic Forces and Endothelial Dysfunctionmentioning
confidence: 99%
“…CMV infection is associated with various chronic inflammatory diseases, including cardiovascular diseases (CVDs) [8] such as myocarditis, atherosclerosis, and coronary artery disease [911]. Hypertension is an important cause of CVDs, and recent studies [1218] have shown that patients with a CMV infection have an increased risk of EH; however, the association between CMV and EH remains unclear, and thus the effect of CMV infection on blood pressure is controversial.…”
Section: Introductionmentioning
confidence: 99%